Plan de marketing para el posicionamiento de la Compañía Confianza Marketing FXAV S.A.S. - Alvarez Urgilés, Xavier Andrés (2023)
The following investigation addresses the reality of the company Confianza Marketing FXAV S.A.S. and presents a solution proposal for its main problem, which is its positioning in the current market. After carrying out the respective investigations, the results of the investigation allowed the general objective and the specific objectives to be achieved, it was possible to corroborate that the company Confianza Marketing FXAV S.A.S., despite all the benefits it offers, is not well known, and needs to start to position itself in the minds of consumers. It was also possible to determine the main communication channels, which revealed without any doubt that they are social networks and the internet, for which the marketing plan focuses heavily on promotion through virtual media based on ATL advertising strategies.